Developing the next generation of university teachers - Hlengwa, Amanda (Critical Studies in Teaching and Learning, 2023)
South Africa’s higher education system requires systemic mechanisms to respond to the urgent, complex, and often competing urgent calls to transform. The New Generation of Academics Programme (nGAP) is an example of a systemic response to the challenges related to the composition and capacity of academic staff to adequately respond to the competing demands placed on higher education. The programme is designed to support public institutions’ recruitment, development and retention of early career academics (DHET, 2016). The programme allows appointees who have limited formal teaching experience access into an academic career. Questions have arisen, though, regarding the development of nGAP appointees as teachers that can contribute to institutional changes in pedagogical approaches and to curriculum development more generally. This study investigates how dominant discursive constructions of teaching, emerging from induction programmes in four institutions, may contribute to shaping a new generation of university teachers.